Adenophora Stricta Root Extract Alleviates Airway Inflammation in Mice with Ovalbumin-Induced Allergic Asthma - Cheol-Jong Jung; Seok-Man Park; Dae-Geon Lee; Yeong-Eun Yu; Tae-Hun Ku; Im-Joung La; Il-Je Cho; Sae-Kwang Ku (MDPI AG, 2023)
Adenophora stricta Miq. (Campanulaceae family) is a traditional herb used for relieving cough and phlegm in East Asia. This study explored the effects of A. stricta root extract (AsE) in ovalbumin (OVA)-induced allergic asthma and lipopolysaccharide (LPS)-stimulated macrophages. Administration of 100-400 mg/kg AsE dose-dependently decreased pulmonary congestion and suppressed the reduction of alveolar surface area in mice with OVA-mediated allergic asthma. Histopathological analysis of lung tissue and cytological analysis of bronchioalveolar lavage fluid showed that AsE administration significantly attenuated inflammatory cell infiltration into the lungs. In addition, AsE also alleviated OVA-specific immunoglobulin E, interleukin (IL)-4, and IL-5 production, which are essential for OVA-dependent activation of T helper 2 lymphocytes. In Raw264.7 macrophage cells, AsE significantly blocked nitric oxide, tumor necrosis factor-α, IL-1β, IL-6, and monocyte chemoattractant factor-1 production in response to LPS. Results from an immunoblot assay revealed that AsE inhibited the phosphorylation of c-jun N-terminal kinase, inhibitory-κB kinase α/β, and p65 in LPS-stimulated cells. Furthermore, 2-furoic acid, 5-hydroxymethylfurfural, and vanillic acid 4-β-D-glucopyranoside in AsE were shown to inhibit the production of proinflammatory mediators by LPS. Taken together, the present results suggest that A. stricta root will be a useful herb for relieving allergic asthma through managing airway inflammation.